Comparative Study between Ringer’s Lactate and Gelofusine as Preloading Infusion in Spinal Anaesthesia for Prevention of Hypotension - Gupta, Birendra; Ghosh, Arup; Ray, Amit; Haldar, Purba; Piplai, Gautam (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Spinal anaesthesia is a form of safe regional anaesthetic technique but sometimes associated with few untoward side effects , most commonly hypotension. This study was planned to compare the efficacy of Ringer’s lactate and Gelofusine as preloading infusion to prevent hypotension, requirement of vasopressors and requirement of total fluid given during surgery under spinal anesthrsia to maintain stable hemodynamics. Methods: 60 male patients undergoing surgery under spinal anaesthesia were randomly allocated into 2 groups. Groups were designated according to the study fluid transfused over 15 minutes as follows: Group R (n=30) - Patients receiving 10ml/kg body weight of Ringer’s Lactate, Group G (n=30) - Patients receiving 10ml/kg body weight of Gelofusine. After preloading, vital parameters were recorded. Subarachnoid block was performed and Vital parameters were recorded at 1, 3, 5, 7, 9, 11, 13, 15, 18, 21, 24, 27, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90 minutes after giving subarachnoid block. All demographic and clinical parameters, level of sensory block, requirement of intraoperative Mephenteramine, intravenous fluid administration and incidence of adverse effects were documented at different points of time and compared accordingly. Results: There was significant difference (p<0.05) in SBP and DBP in the two groups from 5 to 18 minutes. HR differ significantly in the groups from 7 to 18 minutes. Volume of intraoperative fluid and Mephentermine required after spinal anaesthesia is less in patients preloaded with Gelofusine as compared to Ringer’s lactate. Conclusions: Preloading with Gelofusine (colloid) is more effective than Ringer’s lactate (crystalloid) in spinal anaesthesia for prevention of hypotension.